Biophysical Characterization of a Novel SCN5A Mutation Associated With an Atypical Phenotype of Atrial and Ventricular Arrhythmias and Sudden Death - Ghovanloo, Mohammad-Reza; Atallah, Joseph; Escudero, Carolina A.; Ruben, Peter C. (Frontiers in Physiology, 2020)
Background: Sudden cardiac death (SCD) is an unexpected death that occurs within an hour of the onset of symptoms. Hereditary primary electrical disorders account for up to 1/3 of all SCD cases in younger individuals and include conditions such as catecholaminergic polymorphic ventricular tachycardia (CPVT). These disorders are caused by mutations in the genes encoding cardiac ion channels, hence they are known as cardiac channelopathies. We identified a novel variant, T1857I, in the C-terminus of Nav1.5 (SCN5A) linked to a family with a CPVT-like phenotype characterized by atrial tachy-arrhythmias and polymorphic ventricular ectopy occurring at rest and with adrenergic stimulation, and a strong family history of SCD. Objective: Our goal was to functionally characterize the novel Nav1.5 variant and determine a possible link between channel gating and clinical phenotype. Methods: We first used electrocardiogram recordings to visualize the patient cardiac electrical properties. Then, we performed voltage-clamp of transiently transfected CHO cells. Lastly, we used the ventricular/atrial models to visualize gating defects on cardiac excitability. Results: Voltage-dependences of both activation and inactivation were right-shifted, the overlap between activation and inactivation predicted increased window currents, the recovery from fast inactivation was slowed, there was no significant difference in late currents, and there was no difference in use-dependent inactivation. The O’Hara-Rudy model suggests ventricular afterdepolarizations and atrial Grandi-based model suggests a slight prolongation of atrial action potential duration. Conclusion: We conclude that T1857I likely causes a net gain-of-function in Nav1.5 gating, which may in turn lead to ventricular afterdepolarization, predisposing carriers to tachy-arrhythmias.